2015
DOI: 10.11114/jets.v4i2.1136
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive Teaching: Examining Teachers’ Understandings and Perspectives

Abstract: This action research study examines a graduate level course on Ethnicity and Education. Eighteen teacher participants enrolled in a Master of Education program. Course instructors analyzed teacher participants' perceptions of culturally responsive teaching. A teaching plan, a post-course questionnaire, a focus group interview, and a follow up questionnaire were collected after the course. Analysis of the data generated three themes: 1) Doing culturally responsive activities; 2) Moving towards culturally respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…These doubts can result in outright resistance to CRE. However, most often they result in teachers’ limiting their perceptions of the usefulness, value, and relevance of CRE to issues of student motivation or engagement rather than seeing it as valuable for academic achievement and rigorous student learning (Aronson & Laughter, 2016; Bianchini & Brenner, 2010; Ebersole, Kanahele-Mossman, & Kawakami, 2016; Farmer, Hauk, & Neumann, 2005). Through her work with administrators and teachers, Young (2010) has found that when defining CRE, teachers rarely make any reference to academic success.…”
Section: Teacher Beliefs and Know-how As Sources Of Resistance To Crementioning
confidence: 99%
“…These doubts can result in outright resistance to CRE. However, most often they result in teachers’ limiting their perceptions of the usefulness, value, and relevance of CRE to issues of student motivation or engagement rather than seeing it as valuable for academic achievement and rigorous student learning (Aronson & Laughter, 2016; Bianchini & Brenner, 2010; Ebersole, Kanahele-Mossman, & Kawakami, 2016; Farmer, Hauk, & Neumann, 2005). Through her work with administrators and teachers, Young (2010) has found that when defining CRE, teachers rarely make any reference to academic success.…”
Section: Teacher Beliefs and Know-how As Sources Of Resistance To Crementioning
confidence: 99%
“…Okuldaki sosyal uyumun başarılı olmasında ise mülteci öğrencilerin okulda karşılaştıkları öğretmen tutumları belirleyici olmaktadır. Bir başka ifadeyle, okullarda karşılaşılan farklı kültür kodlarının nasıl etkileşim ve bütünleşme aracı olarak değerlendirileceği ve kültürel açıdan duyarlı eğitimin hangi bakış açısıyla ele alınacağı ağırlıklı olarak öğretmenin yaklaşımı tarafından belirlenmektedir (Ebersole, Kanahele Mossman ve Kawakami, 2016). Dolayısıyla mülteci öğrencilerin gerek akademik süreçlere etkin katılımlarının gerek içine dahil oldukları yeni kültürel bağlama uyumlarının sağlanmasında öğretmenin bu süreci iyi tanımlaması, sorunların kaynağını iyi anlaması ve öğrencilerin temel özelliklerini ve sahip olduğu kaynakları iyi değerlendirerek belirli stratejiler uygulamaya koyması gerektiği açıktır.…”
Section: Kültüre Duyarlı Eğitimunclassified
“…However, these studies mostly focus on discovering the perceptions and opinions of teachers and prospective teachers. Thus, considering that we were not able to find a study on culturally responsive teaching within the scope of teacher training, except for a study conducted by Ebersole et al (2016), we believe that this study will contribute to filling a significant gap in the literature. Indeed, there are certain questions which teachers must ask themselves in face of differences in the teaching-learning environment.…”
mentioning
confidence: 97%
“…Gay (2002) states that this is possible through teachers' becoming culturally responsive to ethnically different students in their own teaching processes. Ebersole, Kanahale-Mossman, and Kawakami (2016) go beyond theoretical study, examining themes such as conducting culturally responsive activities, moving toward culturally responsive teaching as a perspective, and being a culturally responsive teacher and conclude that it is necessary to reconceptualize culture-based courses to deepen teacher perspectives rather than merely enhancing teaching activities which support culturally responsive teaching and learning.…”
mentioning
confidence: 99%